The power of controversy: compensatory consumption among younger and older consumers - Hieber, Carina (2022)
The prevalence of belief-driven buying has never been more apparent than today. This study on compensatory consumption proposes brand controversy as a potentially enticing factor for younger individuals to compensate for powerlessness. It is hypothesized that younger individuals feel less powerful as they experience less political power and therefore use controversial brands to escape the aversive state of powerlessness through compensatory purchasing behavior. By performing a scenario-based experiment, no evidence supported the central hypothesis. However, it was discovered that younger individuals feel powerless since they experience less political power than older individuals. The gathered insights will assist companies in determining whether it is advantageous to venture into controversy.